Adalimumab for endoscopic and histopathological mucosal healing in paediatric patients with moderate to severe Crohn’s disease - Edyta Szymanska; Maciej Dadalski; Wieslawa Grajkowska; Sylwia Szymanska; Maciej Pronicki; Jaroslaw Kierkus (Gastroenterology Review)
Introduction : Deep remission, defined as clinical remission with mucosal healing (MH), with anti-tumor necrosis factor (TNF)-α agents is a new target for therapy in Crohn’s disease (CD). Provided that the efficacy of infliximab (IFX) for induction of MH in CD has been demonstrated, there are much less data for adalimumab (ADA), and none concerning MH on histopathological examination. Aim : To assess the impact of biological therapy with ADA on both endoscopic and histopathological MH in paediatric patients with CD. Material and methods : Twenty-three children (10 boys and 13 girls) aged 13.0 ±9.3 years with moderate to severely active CD diagnosed at the mean age of 5.5 ±0.83 years were included into the study. Seven (30.4%) patients had been previously treated with infliximab and switched to ADA due to intolerance or loss of response. Colonoscopy and gastroscopy with sample collection were performed in all patients before and after induction treatment with ADA. Clinical activity of the disease was assessed using the Paediatric Crohn’s Disease Activity Index (PCDAI), and the endoscopic activity was scored using the Simple Endoscopic Score (SES-CD). Histological changes were evaluated by a self-adapted numerical scoring system. Results: Four (17.4%) patients reached clinical remission (PCDAI ≤ 10). When comparing data at baseline and at a week after ADA treatment, a significant decrease was observed in median PCDAI and in SES-CD score between the initial and control colonoscopies. We reported a decrease in histological scale, which was not statistically significant. A correlation was found between PCDAI and SES-CD score. Conclusions : Biological therapy with ADA has a positive impact on endoscopic mucosal healing in paediatric patients with CD, which is not associated with histological evidence of suppression of inflammation. Endoscopic MH correlates better than microscopic one with clinical remission.